Metamorphosis in John Boyne's The Heart's Invisible Furies and Salem Hameed's Banadiq Al Nabi (Rifles of the Prophet) - Hussein, Huda Raheem; Hussein, Fatima Raheem (Al-Adab Journal, 2019)
Religion and literature seem to be standing on two wholly different poles, perspective on the relationship between them has been diverse; however, it either follows: heteronomy, theonomy, or autonomy. The determination of the question "What is literature?" can be based on literary norms alone. But in the evaluation of the greatness of literature (its adequacy, the truth it embodies, etc.) faith must intervene. All notions of what is best and most true in the world depend upon what one deems real, so they are perspective bound, however, these notions should deal with the deepest concerns of human life in which surely the question of religion must come first. This paper tackles two novels by two different novelists of different nationalities. The first is the novel of the Irish novelist John Boyne's The Heart's Invisible Furies (2017), where the church controls the social behaviour of people and enforces the laws that would confine their freedom. It follows the life of Cyril Avery who takes a long time in order to thwart decades of crippling guilt and shame that he was burdened with since his childhood. The second novel is the Iraqi's Salem Hameed's Banadiq Al Nabi (Rifles of the Prophet) (2017) which pictures the life of Asmer bin Shwali, who suffers from schizophrenia, since another voice speaks from within, the voice of the prophet Mani himself or one of his followers. He and the voice within share the same loss of identity and of terrorism stemming from a terrible misunderstanding of religion. Both novels tackle characters shaped by an environment based on religious inclinations and, henceforth, transformed into apostles of a new religion based on humanity alone